Pemanfaatan Bibliografi dan Terbitan Pemerintah di Perpustakaan sebagai Sumber Informasi - Agil Farhan; Bachrul Ilmi; Anggito Hanan Nugroho; Adyssa Zahrani; Alan Chandra Ariefan (Central Library of Universitas Sebelas Maret, 2022)
The library as a source of information must of course provide sources of information that can be utilized by users in meeting their information needs. Libraries must have collections that can support the needs of users by providing reference sources that can be used as sources of information. By providing secondary sources of library information such as bibliographies and government publications. Bibliography and Government Publications are one of the general reference sources that contain various important information that can be useful in information retrieval. The purpose of writing this article is to provide an overview related to the use of bibliography and government publications as a source of information, especially for users to meet information needs. Constraints in the use of Bibliography, namely the user does not know how to use the Bibliography. Meanwhile, obstacles in the use of government publications, namely human resources with educational background in Library Science are still minimal so that management is not optimal, lack of responsibility and initiative for library staff to manage government publications, has not been inputted to a computer which results in difficult retrieval processes and collections of publications are not yet available. neatly arranged. Besides that, so that the general public can take advantage of the services of general reference sources in the library as a reference in finding information.